Servant Leadership: Kunci Peningkatan Kinerja Pelayanan Melalui Employee Engagement: Servant leadership - Nur Aisya, Hania; Amin, Shofia; Hasanah, Nur (Brida Provinsi Jambi, 2025)
Servant leadership is a leadership style that prioritizes service to subordinates and focuses on the holistic development of employees. This leadership approach is often associated with increased employee engagement and improved organizational performance, particularly in public service institutions where service quality is a critical success factor. This study aims to examine the effect of servant leadership on service performance at the Jambi Class I TPI Immigration Office, with employee engagement as a mediating variable. Using a quantitative research approach was employed, involving all 40 employees working in the passport service division. Data were collected using a structured questionnaire and analyzed through Structural Equation Modeling (SEM) with the aid of SmartPLS software. The findings indicate that servant leadership does not have a direct and significant impact on service performance. However, servant leadership positively and significantly influences employee engagement. In turn, employee engagement exerts a strong and significant effect on service performance. These results confirm that employee engagement serves as a full mediator in the relationship between servant leadership and service performance. In other words, the positive effects of servant leadership on service outcomes are channeled entirely through its ability to enhance employees’ emotional commitment, enthusiasm, and psychological investment in their roles.